2004
DOI: 10.1111/j.1535-6841.2004.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

The Geography of Homelessness in American Communities: Concentration or Dispersion?

Abstract: Few recent studies of homelessness have focused on the distribution of the phenomenon across different types of community contexts. Nevertheless, claims are often made about the decline of urban skid rows and the increasing spatial ubiquity of the homeless population. Motivated by these claims, our research analyzes 1990 Census S‐night data at multiple geographic levels to determine whether homeless people remain locationally concentrated or have become more dispersed in the contemporary United States. Data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In addition to their lack of resources and network ties, three characteristics of the homeless population conjoin to make for an unstable and unreliable adherent pool: the episodic, transitory character of homelessness, with estimates of more than 50% cycling on and off the streets two or more times (Burt, Aron, and Lee 2001;Snow and Shockey 1998;Wong and Piliavin 1997); spatial mobility among the homeless within cities, as they often migrate from one service delivery area or "shadow work" node to another during the course of their daily routines (Lee and Price-Spratlen 2004;Snow and Anderson 1993;Snow and Mulcahy 2001); and the demands of day-to-day survival on the streets (Rosenthal 1994;Snow and Anderson 1993;Wagner 1993;Wright 1997).…”
Section: / Social Forcesmentioning
confidence: 99%
“…In addition to their lack of resources and network ties, three characteristics of the homeless population conjoin to make for an unstable and unreliable adherent pool: the episodic, transitory character of homelessness, with estimates of more than 50% cycling on and off the streets two or more times (Burt, Aron, and Lee 2001;Snow and Shockey 1998;Wong and Piliavin 1997); spatial mobility among the homeless within cities, as they often migrate from one service delivery area or "shadow work" node to another during the course of their daily routines (Lee and Price-Spratlen 2004;Snow and Anderson 1993;Snow and Mulcahy 2001); and the demands of day-to-day survival on the streets (Rosenthal 1994;Snow and Anderson 1993;Wagner 1993;Wright 1997).…”
Section: / Social Forcesmentioning
confidence: 99%
“…In a separate paper (Lee & Price-Spratlen, 2002), we offer an extensive justification for taking these data seriously. Our argument rests on the following points:…”
Section: Datamentioning
confidence: 99%
“…As Table 2 suggests, region may be a worthwhile grouping criterion. This possibility receives additional backing from treatments of homelessness that highlight the distinctiveness of the problem in the Northeast or along the West Coast (e.g., the so-called ''Highway 1 homeless'' in California) or that document regional variation in homelessness rates and shelter bed availability (Burt, 1992;Lee & Price-Spratlen, 2002;U.S. Department of Housing and Urban Development, 1984).…”
Section: Understanding Intermetropolitan Variationmentioning
confidence: 99%
“…However, specific neighborhood and community characteristics where homeless adults are housed in these programs and comparisons with previous communities of residence have not been adequately studied. There have been some efforts to examine and characterize the geography of homeless persons through national surveys; for example, finding that homelessness is overrepresented in metropolitan and urban regions (Lee and Price-Spratlen 2004; National Alliance to End Homelessness 2009), but little study of race, income, and education levels of neighborhoods in which they are housed.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that Census data did not predict well-being outcomes of a seriously mentally ill population in supported housing programs, but self-report ratings of the social environment of the neighborhood did (Wright and Kloos 2007). Despite these findings, there continue to be reports that homeless individuals often live in urban skid rows or in ''spaces of containment'' where there are high levels of poverty and social marginalization (Jocoy and Del Casino 2008;Lee and Price-Spratlen 2004).…”
Section: Introductionmentioning
confidence: 99%